THE IMPACT OF DIMENSIONS OF FINANCIAL INCLUSION IN ENHANCING THE BANKING PROFITABILITY "AN APPLIED STUDY OF A SAMPLE OF EGYPTIAN COMMERCIAL BANKS" FOR THE PERIOD (2012-2020) - Dahham Lateef Dahham (Scholar Express Journals, 2023)
The study aimed to measure the impact of financial inclusion on the profitability of commercial banks by taking a sample of public banks in the Egyptian market in the period from (2012 to 2020). With the criterion of using banking services and the criterion of accessing banking services, in contrast, the profitability of commercial banks was measured using the return on ownership and the return on assets, and it was concluded that financial inclusion is statistically significant on the return on assets and the return on ownership. The study recommended building a national strategy to enhance financial inclusion in Egypt and conducting more studies using other indicators of the performance of commercial banks.
Keywords: financial inclusion; profitability; Egyptian commercial banks